Zastosowanie modelu regresji do generowania danych - Zmyślona, Beata (The application of regression model to data generation, 2008)
The most popular methods of statistical inference in the case of incomplete data sets are based on the data augmentation. The multiple imputation and parameter simulation belong to the methods of data augmentation. The main idea of these techniques consists in creating the m complete data sets by replacing each missing data with a set of plausible values, which are generated either from some conditional distribution of missing data or using some imputation model. In this paper, we present the methods of generating data using some regression model and its applying to the analysis of incomplete data of air pollution measurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 28-40